VERBA “MELUKAI” DALAM BAHASA ROTE DIALEK DENGKA: KAJIAN META SEMANTIK ALAMI (MSA) - Efron Erwin Yohanis Loe (SASDAYA: Gadjah Mada Journal of Humanities, 2017)
This article will analyze and examine the verb “to hurt” found in Dengka Dialect of Rote Language. Based on the data collected from the informants, there are nineteen lexicons discovered and each of them will be further described in the discussion part of this article. The nineteen lexicons are: uta, tati, mbau, donggi, dui, undu, teta, ela, kalu, ali, isi, iɁi, tede, soso, nato, edo, ule, tutu and dodo. The approach applied to analyze those nineteen lexicons is natural semantics meta-language (NSM). By using this approach, we would optimise the analysis in order to obtain a better result, since there is only one meaning for each lexicon. The results of this analysis could become a reference for the readers and the researchers in writing articles using their language that related to semantics by using natural semantics meta-language theory.